2013
DOI: 10.1186/1742-4755-10-66
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge on timing of mother-to-child transmission of HIV among antenatal care attending women in Southern Ethiopia: a cross sectional study

Abstract: BackgroundMother-to-child transmission (MTCT) of HIV infection remains a major public health problem and constitutes the most important cause of HIV infection in children under the age of 15 years old. Awareness on MTCT of HIV and knowledge of its timing usually pose a direct effect on utilization of PMTCT services (mainly HIV testing, infant feeding options and antiretroviral use). The objective of this study is to assess pregnant women’s knowledge on timing of MTCT of HIV in Southern Ethiopia.MethodsA cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 11 publications
14
44
1
Order By: Relevance
“…Misconception has the potential of preventing people from taking necessary steps aimed at preventing HIV infection [26]. In keeping with findings in some rural communities in Africa [9], there is worrisome level of misconceptions about HIV/AIDS among inhabitants of rural population in our study. Since inhabitants of rural communities probably are more likely to hold misconceptions about HIV [27], it is very crucial that relevant governments in developing countries design interventions aimed at addressing these misconceptions and empowering the rural dwellers with adequate information on HIV/AIDS.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Misconception has the potential of preventing people from taking necessary steps aimed at preventing HIV infection [26]. In keeping with findings in some rural communities in Africa [9], there is worrisome level of misconceptions about HIV/AIDS among inhabitants of rural population in our study. Since inhabitants of rural communities probably are more likely to hold misconceptions about HIV [27], it is very crucial that relevant governments in developing countries design interventions aimed at addressing these misconceptions and empowering the rural dwellers with adequate information on HIV/AIDS.…”
Section: Resultssupporting
confidence: 62%
“…In keeping with the typical picture seen in rural areas in Nigeria, most of the respondents did not have Primary education. Low level of education among inhabitants in the rural areas contributes to widespread misconceptions about HIV in those areas [9]. Majority of the respondents in this study, not having formal education (52.7%) revealed that the literacy level is low.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, less than half of the women knew that the virus can be transmitted through breastfeeding. Poor knowledge in these areas has been reported among women of reproductive age in the Islamic Republic of Iran (12), Ethiopia (13) and Nigeria (14). Lack of knowledge was shown to be a barrier to women taking appropriate actions for the prevention of mother-to-child transmission, as a higher level of knowledge in this study was associated with desirable intended behaviours related to testing and maintaining healthy sexual relations.…”
Section: Discussionmentioning
confidence: 63%
“…Different studies reported that sociodemographic factors like age [9], urban living [10], higher educational level [11], and being house wife [12] as factors that affect mothers' knowledge of MTCT of HIV. Studies conducted in southern and northwest Ethiopia [10, 12, 13] reported that gravidity, parity, antenatal care (ANC) visits, and male partner discussion are factors associated with good knowledge of mothers on MTCT of HIV.…”
Section: Introductionmentioning
confidence: 99%